2016
DOI: 10.1021/acs.inorgchem.5b02851
|View full text |Cite
|
Sign up to set email alerts
|

Spin Crossover in Dinuclear N4S2 Iron(II) Thioether–Triazole Complexes: Access to [HS-HS], [HS-LS], and [LS-LS] States

Abstract: Access to a new family of thioether-linked PSRT ligands, 4-substituted-3,5-bis{[(2-pyridylmethyl)sulfanyl]methyl}-4H-1,2,4-triazoles (analogues of the previously studied amino-linked PMRT ligands), has been established. Four such ligands have been prepared, PSPhT, PS(i)BuT, PS(t-Bu)PhT, and PS(Me)PhT, with R = Ph, (i)Bu, (t-Bu)Ph, and (Me)Ph, respectively. Three dinuclear colorless to pale green iron(II) complexes, [Fe(II)2(PSRT)2](BF4)4·solvent, featuring N4S2 donor sets, were prepared. Single-crystal structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
74
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(78 citation statements)
references
References 64 publications
4
74
0
Order By: Relevance
“…PSPhT, [27] PS Me PhT, [27] PSiBuT, [27] Pydz Et , [28] Pydz Et/Et , [29] and Pym Et/Me [30] were prepared as reported previously.C omplexes [Co II 2 ( tBuPh Trz Me/Me )(m-BF 4 )](BF 4 ) 3 , [23] [Co II 2 ( pyrr Trz Me/Me )(H 2 O) 2 ](BF 4 ) 4 , [23] [Co II 2 (Pydz Et )(m-Cl)Cl 2 ]Cl, [Co II 2 (Pydz Et/Et )(m-OH)](BF 4 ) 3 · 1 = 2 H 2 O, [29] [Co II (M Et )]BF 4 , [26a] [Co II (M Pr )]BF 4 , [26b] [Co( Br M Et )]BF 4 , [31] [ [24a] [Co III (dmgH) 2 (py)Cl], [32] [Ru-(bpy) 3 ](PF 6 ) 2 , [33] and [Ru(bpy) 3 ]Cl 2 [33] were prepared as previously described.…”
Section: Experimental Section Generale Xperimental Detailsmentioning
confidence: 99%
“…PSPhT, [27] PS Me PhT, [27] PSiBuT, [27] Pydz Et , [28] Pydz Et/Et , [29] and Pym Et/Me [30] were prepared as reported previously.C omplexes [Co II 2 ( tBuPh Trz Me/Me )(m-BF 4 )](BF 4 ) 3 , [23] [Co II 2 ( pyrr Trz Me/Me )(H 2 O) 2 ](BF 4 ) 4 , [23] [Co II 2 (Pydz Et )(m-Cl)Cl 2 ]Cl, [Co II 2 (Pydz Et/Et )(m-OH)](BF 4 ) 3 · 1 = 2 H 2 O, [29] [Co II (M Et )]BF 4 , [26a] [Co II (M Pr )]BF 4 , [26b] [Co( Br M Et )]BF 4 , [31] [ [24a] [Co III (dmgH) 2 (py)Cl], [32] [Ru-(bpy) 3 ](PF 6 ) 2 , [33] and [Ru(bpy) 3 ]Cl 2 [33] were prepared as previously described.…”
Section: Experimental Section Generale Xperimental Detailsmentioning
confidence: 99%
“…Multinuclear SCO complexes have been investigated intensively within the last 15 years, exhibiting promising SCO behaviours for possible applications, in particular binuclear complexes. [57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76] Compared to spin state switching in mononuclear compounds, multinuclear complexes promise more drastic changes of the macroscopic material properties. For instance, the total amount of unpaired electrons -and therefore the magnetic moment -as well as their coupling could accumulate over all metallic centres, increasing interactions compared to those in mononuclear complexes (e.g.…”
Section: 56mentioning
confidence: 99%
“…For the thiadiazole-based ligand 2,5-bis[(2-pyridylmethyl)amino]methyl-1,3,4-thiadiazole with pyridyl donor sidearms, the complexes are in the [LS-LS] state at low temperatures and show a gradual but incomplete spin crossover only above room temperature [19]. Inspired by the fruitful work of S. Brooker et al [21], we herein report the modification of the previous reported ligand [19] by replacing the amino for thioether linkages. The longer C-S bonds compared to the C-N bonds 2 of 10 give greater flexibility of the ligand, and thus, should enable the population of the [HS-LS] and/or the [HS-HS] state at elevated temperatures.…”
Section: Introductionmentioning
confidence: 99%